Molecular assembly and interactions of membrane proteins and viral glycoproteins using mass photometry - Olerinyova, A (2022)
Integral membrane proteins (IMPs) and their interactions form the basis underlying many processes essential for life of all living organisms. Despite their pivotal importance, they are challenging to study due to the presence of a bilayer-embedded transmembrane domain requiring astute strategies to achieve solubilisation in aqueous environments. Here we present mass photometry as a novel technique to investigate IMPs and their interactions in a variety of membrane mimetic systems, uncovering the interactions underlying the bacterial outer membrane architecture. We then apply mass photometry to viral membrane glycoproteins, the HIV-1 envelope spike and SARS-CoV-2 spike, and their interactions with a soluble inhibiting protein and host cell receptor, respectively. In both cases, we describe how the oligomeric nature of the involved proteins facilitates intermolecular crosslinking, facilitating enhanced inhibition.